2006
DOI: 10.1055/s-2006-927090
|View full text |Cite
|
Sign up to set email alerts
|

Stauungspapille bei Gehirnabszess assoziiert mit isolierter persistierender linker Vena cava superior mit Drainage in den linken Vorhof

Abstract: Congenital heart disease such as LSVC is rare. The association of LSVC with papilloedema and brain abscess is very rarely seen. However, the complications of LSVC can be life-threatening. Therefore in children with papilloedema, intraocular and intraorbital reasons as well as congenital heart disease as the underlying reason should be included in the differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After a detailed literature review, 12 case reports were found that discussed right to left shunt as a possible etiology for recurrent brain abscess formation [6][7][8][9][10][11][12][13][14][15][16][17]. The oldest reported case among the 12 case reports was published in 1971 [16].…”
Section: Methodsmentioning
confidence: 99%
“…After a detailed literature review, 12 case reports were found that discussed right to left shunt as a possible etiology for recurrent brain abscess formation [6][7][8][9][10][11][12][13][14][15][16][17]. The oldest reported case among the 12 case reports was published in 1971 [16].…”
Section: Methodsmentioning
confidence: 99%